Frequency of Significant Non-Infarct Related Multi-Vessel Coronary Artery Disease in Patients after the first Presentation with St-Elevation Myocardial Infarction - Muhammad Qasim Khan, Muhammad Shahzad Azeem, Muhammad Waqas, Asma Shareef (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To determine the frequency of significant non-infarct related multi-vessel coronary artery disease in patients after the first presentation with ST-elevation myocardial infarction. Methodology: A minimum of 100 consecutive patients from the department of cardiology, Mayo Hospital Lahore, who fulfilled the inclusion/exclusion criteria were selected. Percentage stenosis in non-IRA was calculated by using quantitative coronary analysis (QCA) software. Results: A total of 100 patients were enrolled in this study. There were 73(73.0%) males and 27(27.0%) females. The mean age of patients was 47.6±19.2 years. Out of 100 patients with STEMI, 42(42.0%) had non-IRA. Among non-IRA, 24(57.1%) had double vessel CAD and 18(42.9%) had triple vessel CAD. Conclusion: Significant non-infarct related multivessel coronary artery disease was common among patients after the first presentation with ST-elevation myocardial infarction.